2013
DOI: 10.1097/adm.0b013e31829b1a6c
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Model for Treating Chronic Hepatitis C in Patients With Psychiatric Disorders, Substance Abuse, and/or Housing Instability

Abstract: An intensive, multidisciplinary treatment approach toward HCV infection treatment can achieve favorable results even in persons traditionally considered to be "poor treatment candidates." Programs aimed at bringing HCV infection treatment to this population are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…These studies demonstrated that patients with ongoing drug use and psychiatric comorbidity-- those traditionally excluded from systems of care-- can be effectively linked to care from and sometimes treated within these settings (Bruce et al, 2012; Jack, Willott, Manners, Varnam, & Thomson, 2009; McAllister et al, 2014; Morano et al, 2014; Newman et al, 2013; Seidenberg et al, 2013). One study implemented an integrated, multidisciplinary medical group visit to integrate care (Ho et al, 2013). In primary care settings where providers lacked experience treating HCV, the Extension for Community Healthcare Outcomes model (Project ECHO) provided tele-health consultation that demonstrated equivalent SVR rates between remote tele-health sites and a specialty HCV clinic in an academic center (Arora et al, 2011).…”
Section: Results: Intervention Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies demonstrated that patients with ongoing drug use and psychiatric comorbidity-- those traditionally excluded from systems of care-- can be effectively linked to care from and sometimes treated within these settings (Bruce et al, 2012; Jack, Willott, Manners, Varnam, & Thomson, 2009; McAllister et al, 2014; Morano et al, 2014; Newman et al, 2013; Seidenberg et al, 2013). One study implemented an integrated, multidisciplinary medical group visit to integrate care (Ho et al, 2013). In primary care settings where providers lacked experience treating HCV, the Extension for Community Healthcare Outcomes model (Project ECHO) provided tele-health consultation that demonstrated equivalent SVR rates between remote tele-health sites and a specialty HCV clinic in an academic center (Arora et al, 2011).…”
Section: Results: Intervention Strategiesmentioning
confidence: 99%
“…The remaining 17 interventional studies are detailed further in Table 4. While some of the adherence-promoting interventions described here did define optimal adherence using the 80/80 rule (Alam, Stainbrook, Cecil, & Kistler, 2010; Carrion et al, 2013), others defined adherence by attendance at study visits (Ho et al, 2013) or treatment completion (Bertino et al, 2010; Bonkovsky et al, 2008). The latter concept technically refers not to adherence, but treatment persistence, which is a closely related construct that is the continuation of prescribed treatment over time (Bae, Guyer, Grimm, & Altice, 2011).…”
Section: Results: Intervention Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, multidisciplinary teams include physicians, nurses, mental health and counselling services, social work and advocacy as well as services related to problematic substance use (Bruggmann & Litwin, 2013). Close collaboration within these models is viewed as essential to success with the multidisciplinary model providing a forum for interaction in which the providers support each other while providing supports to patients (Ho et al, 2013).…”
Section: Multidisciplinary Approachmentioning
confidence: 99%